2006
DOI: 10.1097/01.prs.0000221875.24467.2d
|View full text |Cite
|
Sign up to set email alerts
|

Rhinoplasty Model in Rabbit

Abstract: This experimental model for rhinoplasty has not been reported in any previous studies. This study demonstrates the surgical anatomy of the rabbit in detail and constitutes a guide for researchers as a convenient experimental model for rhinoplasty, with all stages similar to those performed on humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Several animal models are used in rhinoplasty and nose cartilage tissue-engineering studies. Rabbit models are frequently used due to their affordability and availability, and surgical procedures for rabbits are well-defined [123,124]. However, leporine nasal cartilage is significantly less cellular and has different shapes and thicknesses than human cartilage [125].…”
Section: 5: Validation Of Engineered Nasal Cartilagesmentioning
confidence: 99%
“…Several animal models are used in rhinoplasty and nose cartilage tissue-engineering studies. Rabbit models are frequently used due to their affordability and availability, and surgical procedures for rabbits are well-defined [123,124]. However, leporine nasal cartilage is significantly less cellular and has different shapes and thicknesses than human cartilage [125].…”
Section: 5: Validation Of Engineered Nasal Cartilagesmentioning
confidence: 99%
“… 17 It has been reported that when the basement membrane is intact after injury, the respiratory epithelium restores to its normal height after several days, but when the basement membrane is damaged, regeneration takes several weeks with the formation of squamous or transitional epithelium. 10 The subepithelial glands are not always regenerated, and the lamina propria may be substituted by dense connective tissue. 4 A circular wound created in rabbit sinus mucosa decreased in size concentrically with a speed of 20 μm/hour at the initial stage and decreased to 4–5 μm/hour after 7 days.…”
Section: Discussionmentioning
confidence: 99%
“… 4 A circular wound created in rabbit sinus mucosa decreased in size concentrically with a speed of 20 μm/hour at the initial stage and decreased to 4–5 μm/hour after 7 days. 10 However, the regeneration time of a septal mucosal defect, has not been reported in the literature so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previously-proposed rabbit in vivo model may address some of these issues. 2 However, the prohibitive cost of live animal models would prevent that from becoming a widely applicable educational tool. On the other hand, isolating the cartilaginous framework of the nasal tip in our proposed model may in fact be advantageous for tip mechanics research.…”
Section: Discussionmentioning
confidence: 99%